First Case of Bartonella henselae Bacteremia in Korea - Im, Jae-Hyoung (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2013)
Bartonella henselae causes cat-scratch disease, bacteremia, and various focal infections. Despite the worldwide occurrence of B. henselae infections, reports in humans are rare in Korea. The clinical manifestation of all 5 previously reported cases was lymphadenopathy. Herein, we report a case of bacteremia in a woman who presented with prolonged fever. B. henselae was isolated from a blood specimen by cell culture. Conventional polymerase chain reaction amplification and sequencing of the 16S-23S rRNA intergenic space region confirmed the isolate to be B. henselae. The patient had no underlying immunocompromising conditions and no recent exposure to animals. She was successfully managed with a combination of doxycycline and hydroxychloroquine.